ANALISIS KETERAMPILAN PROSES SAINS SISWA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING MELALUI EKSPERIMEN UJI ZAT MAKANAN SEDERHANA - Ai’sya Khoirunnisa; Anggi Sintia Meilani; Delia Novita; Iwan Ridwan Yusup; Susanti Ichsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the level of science process skills of students at Mekar Arum Junior High School. The research method used is quantitative research using experimental methods with purposive sampling techniques. In the learning process, using the discovery learning model by conducting experiments through simple food substance tests. It was found that overall the indicators of science process skills of students in class VIII.A SMP Mekar Arum had an average of 72.85% with a good category, where there were 50% students with low KPS categories or as many as 14 students, 28.60% students with moderate KPS categories or as many as 9 students, and 21.40% students with high KPS categories. This shows that the average KPS of students in class VIII.A is good and should be more frequently trained and used in learning activities, so that students have all the abilities needed to obtain, develop, and apply science concepts, principles, laws or theories.